The Effect of Career Placement and Development to Employee Performance - Siska Yunanti (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
Employee performance, in general, is an embodiment of work carried out by employees who are usually used as a basis or reference for evaluating employees in an organization. Good performance is a step towards achieving organizational goals, therefore, performance is also a deciding tool in achieving organizational goals so it needs to be strived to improve employee performance. This study aims to study the Placement and Career Development of employee performance at PT. Jakarta Prima Cranes in Jakarta. The method used is explanatory research with a sample of 53 respondents. The analysis technique uses statistical analysis with regression testing, evaluation, determination, and hypothesis testing. The results of this study indicate the significance of the company's performance of 48.2%, the hypothesis test obtained significance of 0,000 <0.05. Career Development has a significant effect on employee performance by 59.6%, hypothesis testing obtained significance of 0,000 <0.05. Career Placement and Development simultaneously have a significant effect on employee performance by 56.3%, hypothesis testing obtained significance of 0,000 <0.05.